Short Communication: Population dynamics of double-spined rock lobster (Panulirus penicillatus Olivier, 1791) in Southern Coast of Yogyakarta - RAKHMA FITRIA LARASATI; SUADI SUADI; EKO SETYOBUDI (Biodiversitas Journal of Biological Diversity, 2018)
Larasati RF, Suadi, Setyobudi E. 2018. Short Communication: Population dynamics of double-spined rock lobster (Panulirus penicillatus Olivier, 1791) in Southern Coast of Yogyakarta. Biodiversitas 19: 337-342. The southern coast of Yogyakarta, Indonesia, near to the Indian Ocean borders is a preferable habitat for lobster. Double-spined rock lobster (Panulirus penicillatus) is one of the prevalent species caught by fishermen. However the increased number of capture activities had an effect on the sustainability of global lobster fisheries. In order to sustain these fisheries resource, the preservation management of lobster should include wild stock assessments. Currently, the effect of fishing pressures on populations of P. penicillatus is limited. The objective of this research was to identify several factors affecting lobster population in terms of growth (carapace length (CL) and mass), recruitment, mortality rates, and exploitation rates in this species. Results showed that double-spined rock lobster had a longer size (CL) (45.2-55.1 mm) than that of females (55.2 mm-65.1 mm). While the growth rate (K) of males lobster is 0.85 year-¹ and its CL reached an asymptotic point at 125 mm (12 years old). Growth rate of females double-spined rock lobster was 0.55 year-¹ and its CL reached an asymptotic point at 125.5 mm (15 years old). The total estimation of mortality rates of double-spined rock lobster was 2.46, wherein 2.56 year-¹ for males and females, respectively. The estimated values of M were 1.08, 0.81 year-¹ for males and females, respectively while the respective values of F were 1.38 year-¹ and 1.75 year-¹ for males and females. The exploitation rate of males was 0.56 and females was 0.68. It has exceeded the optimal level (0.5) and reached overfishing value. Based on these results, it suggest that the time management of fishing activities such as by several approaches including the restricted time of fishing activity in spawning and recruitment season, the management of catching effort by the development of environment-friendly fishing gear, and the development of the lobster hatchery to reproduce and maintain their population naturally.